Ithbāt Ṭalāq: An Offer of Legal Solutions to Illegal Divorce in Indonesia - Firman Wahyudi (Al-Ahkam, 2022)
The dispute between Islamic law and positive law is continuously ongoing regarding the practice of illegal divorce. This practice is valid in Islamic law as long as the conditions and pillars are fulfilled. However, in Islamic law, it is considered a violation of marriage norms. The urgency of this study lies in the discourse of ithbāt ṭalāq to bridge the rise of illegal divorce in society. Through a literature review with a juridical approach to finding a legal basis for a case in concreto, this article shows that ithbāt ṭalāq functions as an instrument that can solve disputes between Islamic law and positive law. Through this instrument, husbands who force divorce out of court can be considered criminal actors who must be given sanctions in the form of ta'zīr (fine).